Ultra‐short‐course booster is effective in recurrent grass pollen‐induced allergic rhinoconjunctivitis. Issue 1 (5th September 2017) - Pfaar, O.; Lang, S.; Pieper‐Fürst, U.; Astvatsatourov, A.; Gerich, F.; Klimek, L.; Kramer, M. F.; Reydelet, Y.; Shah‐Hosseini, K.; Mösges, R.
Abstract: Background: A relevant proportion of allergic rhinoconjunctivitis (ARC) patients experience recurrent symptoms after successfully completing allergen immunotherapy (AIT). This prospective, controlled, noninterventional study used internationally standardized instruments to determine the clinical effects of a preseasonal, ultra‐short‐course booster AIT on clinical outcome parameters. Methods: This two‐arm study included patients aged ≥12 years with recurrent grass pollen‐induced seasonal AR who had completed a successful course of any grass pollen AIT at least 5 years before enrolment. Overall, 56 patients received one preseasonal short‐course booster AIT using tyrosine‐absorbed grass pollen allergoids containing the adjuvant monophosphoryl lipid A (MPL ® ); 51 control patients received symptomatic medication. The combined symptom and medication score (CSMS) was recorded in the (peak) grass pollen season. Furthermore, concomitant (antiallergic) medication use, the patients' state of health, Mini Rhinoconjunctivitis Quality of Life Questionnaire (MiniRQLQ) results and safety/tolerability of the treatment were assessed. Results: The CSMS in the peak grass pollen season was significantly lower in the booster AIT group (Δ=38.4%, P <.01). Moreover, significantly more patients in this group used no concomitant antiallergic medication throughout the peak grass pollen season. Twice as many patients in the booster AIT group as in the control group reported having a better state of health than in the preceding season. MiniRQLQ results showed significant differences favouring the booster AIT. The booster AIT was generally well tolerated, with only two patients reporting mild, grade 1 systemic adverse events. Conclusion: Booster AIT using tyrosine‐absorbed allergoids containing the adjuvant MPL ® effectively prevents re‐occurrence of symptoms in patients with grass pollen‐induced ARC.